Annual Plan 1995-96 Draft Proposals Volume-III Sectoral Programmes Social Services and General Services Chapter X-XI Government of Meghalaya - Planning Commission (Planning Commission, 1995)
The mid torm apprais of the Eighth Five Year Plan had indicated some of the strengs and weaknesses of the education system In the state. While conmderabl samount of assts infrastructural facilities have been cretcd, the vetnent in some a s fall far short of the targets. Dairing the last ce years a good number of post of teacher s have been so tioae l at the primary, topper primary, Secondary and higher seconda level; a good number of pe n nc and durable schod building sami class rooms have been constructed ; nd basic faciliies like furnitare, text books etc. have been provided, Te h;rs have been trained and given service training to improve their capability. At ti e s condary an higher secondary sector, tangible achievements have shown :,y w.iy i f pro vision of ottildin laboratories in 3 secondary schools.
Planning Department Government of Meghalaya